2018
DOI: 10.1021/acsenergylett.8b00110
|View full text |Cite
|
Sign up to set email alerts
|

Unilamellar Metallic MoS2/Graphene Superlattice for Efficient Sodium Storage and Hydrogen Evolution

Abstract: Unilamellar metallic nanosheets possess superiority for electrochemical energy storage and conversion applications compared to the few-layered bulk and semiconducting counterparts. Here, we report the utilization of unilamellar metallic 1T phase MoS 2 nanosheets for efficient sodium storage and hydrogen evolution through a MoS 2 /graphene superlattice. The superlattice-like assembly composed of alternately restacked unilamellar MoS 2 and modified reduced graphene oxide nanosheets was prepared by a facile solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
164
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 198 publications
(168 citation statements)
references
References 66 publications
4
164
0
Order By: Relevance
“…Differently, two new broad peaks in low‐angle region (marked by #1 and #2) are observed. The calculated d ‐spacing of peak #1 is 1.0–1.2 nm, which should be ascribed to the distance of adjacent MoS 2 monolayers . In addition, the d ‐spacing of peak #2 is about 0.5 nm, which is assigned to the distance between GR monolayer and MoS 2 monolayer .…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…Differently, two new broad peaks in low‐angle region (marked by #1 and #2) are observed. The calculated d ‐spacing of peak #1 is 1.0–1.2 nm, which should be ascribed to the distance of adjacent MoS 2 monolayers . In addition, the d ‐spacing of peak #2 is about 0.5 nm, which is assigned to the distance between GR monolayer and MoS 2 monolayer .…”
Section: Resultsmentioning
confidence: 86%
“…Owing to the electrostatic attraction of opposite charges, the MoS 4 2− anions ionized from (NH 4 ) 2 MoS 4 can easily combine with the amines in PEI−GO, resulting in the modification of MoS 4 2− anions on PEI−GO basal plane (MoS 4 2− /PEI−GO). Moreover, stacked layers of MoS 4 2− /PEI−GO generate via the electrostatic attraction‐induced self‐assembly approach, as the electrostatic forces can trigger the spontaneous stack of the MoS 4 2− /PEI−GO layers . Subsequently, an annealing process was applied at 750 °C under H 2 /Ar atmosphere.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To enhance the HER activity of MoS 2 , theoretical and experimental studies have proposed anchoring of Co atoms and cobaloxime on the inert basal plane of MoS 2 , engineering in the defects sites and using metallic 1T‐MoS 2 . Remarkable advances in heterostructure designs such as MoS 2 /graphene superlattices, nanosized MoS 2 /graphene hybrids, nonmetal plasmonic MoS 2 /TiO 2 heterostructure and MoS 2 ‐WS 2 heterostructures by physiochemical process have led to enhanced HER activity . Some studies have also revealed enhanced HER activity by virtue of active sites …”
Section: Introductionmentioning
confidence: 99%